Cold reactive collisions between laser-cooled ions and velocity-selected neutral molecules - Willitsch, S; Bell, M; Gingell, A; Procter, S; Softley, T (American Physical Society, 2008)
We report a new experimental method to study reactive ion-molecule collisions at very low temperatures. A source of laser-cooled ions in a linear Paul trap has been combined with a quadrapole-guide velocity selector to investigate the reaction of Ca+ with CH3F at collision energies Ē_coll/ k_B ≥ 1 K with single-particle sensitivity. The technique represents a general approach to study reactive collisions between ions and polar molecules over a wide temperature range down to the cold regime.